IMPLEMENTASI KEBIJAKAN COMMON EUROPEAN ASYLUM SYSTEM (CEAS) JERMAN DALAM PENERIMAAN PENGUNGSI, 2015-2017 - Muharjono Muharjono; Vidi Marentra Eflar (Jurnal Studi Diplomasi dan Keamanan, 2018)
Migration in Germany has a long history. The refugee crisis has made Germany become a main destination for refugees from the Middle East. As one of the European Union (EU) member countries, Germany could not make asylum rules based on its own regulation, but also must carry out the EU rules. In this case, EU has asylum regulation in its region through Common European Asylum System(CEAS). CEAS is a system that presents common minimum standards regarding the treatment of asylum seekers in EU member countries. This study will analyze how the implementation of CEAS by Germany in receiving refugees, especially from the Middle East in 2015-2017. This research will use descriptive qualitative method with data collection techniques through library research such as books, journals, documents, newspapers, articles and internet sources. It is analyzed by the concept of implementing public policies and concept of international regimes.